Macrosiphoniella remaudierei, a new species of aphid on Helichrysum in Iran (Hemiptera, Aphididae) - Barbagallo, Sebastiano (Zookeys, 2016)
Abstract. A new species of aphid, belonging to the genus Macrosiphoniella Del Guercio, 1911, is described using three samples collected in Iran on Helichrysum armenium (Asteraceae, Inuleae) by the late Prof. G. Remaudière. Both apterous and alate viviparous females of the new taxon, Macrosiphoniella remaudierei sp. n., are described and compared to corresponding morphs of the closely allied Macrosiphoniella aetnensis and to other congeneric aphid species on Helichrysum in the Palaearctic region. Type specimens are now stored in the Muséum national d’Histoire naturelle in Paris.